2020
DOI: 10.21061/jvs.v6i1.150
|View full text |Cite
|
Sign up to set email alerts
|

The Stigmatized Hero? A Review of UK Opinion Polls and Surveys on Perceptions of British Veterans in UK Society

Abstract: Findings from representative opinion polls and surveys provide information on pertinent perceptions of veterans in British society. The present project compares these findings and contrast publicly pertinent perceptions of veterans with factually correct information. This allows researchers to determine erroneous and stereotyped perceptions of veterans that may be held by members of the British society. The present project reviewed 41 veteran-related question-items from 11 surveys/polls and grouped these quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…This much-cited statistic justifiably underpinned extensive subsequent research which found that the nature of their offences, the circumstances of their incarceration, the challenges they face in prison, and their likelihood of reoffending all seem to be defined to a greater or lesser extent by this prior military experience (e.g. Albertson et al, 2015Albertson et al, , 2017Fossey et al, 2017;McManus and Wood, 2017;Phillips, 2020). By comparison, and despite a now extensive body of research into prison staff and prison management, we know very little about how many prison staff are ex-military.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This much-cited statistic justifiably underpinned extensive subsequent research which found that the nature of their offences, the circumstances of their incarceration, the challenges they face in prison, and their likelihood of reoffending all seem to be defined to a greater or lesser extent by this prior military experience (e.g. Albertson et al, 2015Albertson et al, , 2017Fossey et al, 2017;McManus and Wood, 2017;Phillips, 2020). By comparison, and despite a now extensive body of research into prison staff and prison management, we know very little about how many prison staff are ex-military.…”
Section: Introductionmentioning
confidence: 92%
“…In England and Wales, a key report published in 2014 found that VICs constituted around 7% of the prisoner population (HM Inspectorate of Prisons, 2014), making them the single largest occupational group (Wainwright et al., 2017, p.741). This much‐cited statistic justifiably underpinned extensive subsequent research which found that the nature of their offences, the circumstances of their incarceration, the challenges they face in prison, and their likelihood of reoffending all seem to be defined to a greater or lesser extent by this prior military experience (e.g., Albertson, Banks & Murray, 2017; Albertson, Irving & Best, 2015; Fossey et al., 2017; MacManus & Wood, 2017; Phillips, 2020). By comparison, and despite a now extensive body of research into prison staff and prison management, we know very little about how many prison staff are ex‐military.…”
mentioning
confidence: 99%
“…This much-cited statistic justifiably underpinned extensive subsequent research related to this cohort (e.g. Albertson et al, 2017; Fossey et al, 2017; MacManus & Wood, 2017; Phillips, 2020). Whilst we do not suggest that VICs are undeserving of the considerable research attention they have attracted, this percentage is self-evidently only a fraction of that constituted by ex-military prison officers within their own workforce.…”
mentioning
confidence: 72%
“…Women veterans might have good reasons to hold contradictory feelings about their military service (especially those who have experienced sexual trauma or discrimination during their military careers), and they can feel unrecognized and unacknowledged by the public (Welland, 2021). Finally, there are studies on public opinion (Latter et al, 2018; Phillips, 2020), audience responses (Pitchford-Hyde, 2022) and veterans’ own perspectives on public or media perceptions (Parry and Thumim, 2017; Schmidt, 2020; Smith and True, 2014). In his qualitative survey of veteran student groups in the US, Schmidt (2020) found respondents largely critical of news coverage of veterans and service members, with common themes of an excessive focus on psychological problems, demeaning portrayal (broken, unintelligent), excessive heroic portrayal (over-glorification), or insufficient coverage.…”
Section: Veterans In the Media And On The Mediamentioning
confidence: 99%
“…As we detail below, there is a growing research interest in ‘veteran studies’ from a range of disciplines, especially regarding the challenges associated with transition from military to civilian life (Castro and Dursen, 2019), but the relationship between veteran identity and perceptions of (post)-military representations remains largely under-researched, at least in the UK context. There is a concern that negative or misleading stereotypes of veterans among publics could hinder their successful reintegration into society (Phillips, 2020; Smith and True, 2014), but we are interested in how veterans judge such representations across popular culture, how they construct a sense of ‘public’ audience in their reflections, and the nature of the veteran identity they project within the survey responses. Our survey primarily asked about representation on television, but responses often included reflections beyond televised genres.…”
Section: Introductionmentioning
confidence: 99%